DDoS detection and defense mechanism based on packet analysis and machine learning / Mohd Azahari Mohd Yusof - Mohd Yusof, Mohd Azahari (2019)
DDoS attacks are one of the most serious threats nowadays. It is an attack launched by an attacker using various source of IP addresses to disrupt a network or IoT environment. There are several types of DDoS attacks such as TCP SYN flood, UDP flood, ICMP/Ping flood, Ping of Death, Smurf, Slowloris, HTTP flood, Zero-day attack and SIDDoS which can be launched by attackers for a specific purpose.